Wireless Optogenetics: An Exploration of Portable Microdevices for Small Animal Photostimulation. (2015) - Kale, Rajas P.; Kouzani, Abbas Z.; Berk, Michael; Walder, Ken; Berk, Julian; Tye, Susannah J.
Abstract: Preclinical research in optogeneticneuromodulation in small laboratory animals allows far greater control of neural circuitry. This precision provides an enhanced opportunity for understanding the neural basis of behavior. However, behavioral neuroscience research is limited by conventional benchtop optogenetic systems. By necessity, the animal is tethered to the light source external to the testing environment. Portable optogeneticmicrodevices enhance the potential for valid behavioral testing in naturalistic conditions by eliminating tethering and enabling free and unrestricted movement. This paper reviews recent advances in the development of portable optogeneticmicrodevices supported by wireless power transfer. Light sources and fiber coupling are common problems in optogenetic systems and are addressed. Device designs and parameters are summarized, along with advances in component technology for energy storage and distribution that make these devices possible.